Kinerja Protokol Routing AODV Terhadap Serangan Wormhole Pada Jaringan Mobile Ad Hoc Network (MANET) - Ahmad Hanif AR; Primantara Hari Trisnawan; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
MANET is a wireless architecture network consisting of several mobile devices. It doesn't need any infrastructure or central access point like base station. MANET has 3 types of protocols, namely reactive routing protocol, proactive routing protocol, and hybrid routing protocol. AODV is an example of reactive routing protocol. MANET is still vulnerable to various forms of attacks which are capable to modify, harm, and delete the information data. One of the attacks that can occur in MANET is wormhole attack. Wormhole attack is an attack involving two or more attacking nodes connected in a tunnel, and manipulate the routing and also is able to do packet drop and selective packet drop. Testing is done with OMNET++ network simulator with a various scenarios like number of nodes, number of attacker nodes, and mobility nodes. Testing parameters includes end-to-end delay mean, throughput, packet delivery ratio (PDR), and packet loss. The results show that lowest value of PDR is 27.4% in 10 node with 2 attacker using gauss markov mobility scenario. The lowest value of packet loss is 46 from 2000 sent packet from source node in 30 node with 0 attacker using random waypoint mobility. The lowest mean of end-to-end delay is 8.5ms in 30 node with 4 attacker using random waypoint mobility.